2000
DOI: 10.2486/indhealth.38.205
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms of Seven Heavy Metals in Plasma, Erythrocytes and Urine in Men. Observation in Metal Workers.

Abstract: To elucidate circadian rhythms (variation within a day) of 7 toxic or essential metals in plasma and erythrocytes in relation to the rhythms in urine in men, 19 male metal foundry workers were examined; they were exposed to lead (Pb), zinc (Zn) and copper (Cu) occupationally but separated from the exposure during the study. Circadian rhythms were found for plasma concentration of Pb, cadmium (Cd), Zn, Cu and chromium (Cr) in the workers. Circadian rhythms were also found for Pb, inorganic mercury (Hg), Zn and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…This finding corresponds with studies of cisplatin lethality in Mus musculus (Hrushesky 1985). Furthermore, studies with human subjects have shown a similar circadian rhythm pattern for plasma concentrations of cadmium (Subramanian and Meranger 1984;Yokoyama et al 2000).…”
Section: Discussionsupporting
confidence: 78%
“…This finding corresponds with studies of cisplatin lethality in Mus musculus (Hrushesky 1985). Furthermore, studies with human subjects have shown a similar circadian rhythm pattern for plasma concentrations of cadmium (Subramanian and Meranger 1984;Yokoyama et al 2000).…”
Section: Discussionsupporting
confidence: 78%
“…Lower U-Cd/h in UON samples has also been seen by others (Yokoyama et al 2000). One reason for this could be an increased excretion rate of Cd when urinary flow rate (UF) increases, since UF is higher in daytime than overnight.…”
Section: Cadmium Excretion Ratementioning
confidence: 65%
“…Similar patterns emerged with both male and female subjects, adding validity to the argument that the time of day may have some effect on the blood lead concentrations. A circadian rhythm for lead in plasma, erythrocytes and urine has been noted previously [11,12].…”
Section: Seasonal and Diurnal Variations In Blood Lead Concentrationsmentioning
confidence: 99%